The Effectiveness of Electro-acupuncture in Reducing Body Weight in Obese Patients: A Meta-Analysis - Mutiah, Nurmila; Murti, Bhisma; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Obesity is a problem that is starting to be found, not only in urban areas with high socioeconomic status but also in children living in rural areas, even from middle to lower socioeconomic groups. This study aimed to examine the effectiveness of electro-acupuncture in obesity cases.Subjects and Method: Meta-analysis was carried out with PICO: The population in this study were obese patients aged 16-65. The intervention was in the form of electro-acupuncture therapy. Comparison in the form of sham/ placebo acupuncture. The outcome is weight loss. A meta-analysis study was applied with electronic data sources: Clinical Key, Google Scholar, MEDLINE/PubMed, Science Direct, Scopus. The articles included were full-text with a Randomized Control Trial (RCT) study design. There were 10 articles used in this study with a sample size of 818 people who were divided into two groups (455 people in the acupuncture group and 363 people in the sham/placebo acupuncture group). Articles were analyzed using the Review Manager 5.4 application. The data were analyzed using Standardized Mean difference (SMD) and the heterogeneity of the research sample.Results: There was high heterogeneity between one experiment and another (I2= 86%; p<0.001), so the Random Effect Model (REM) was used. Electroacupuncture therapy was effective in reducing body weight with a Standardized Mean Different (SMD) of 0.50 compared to false acupuncture (SMD= -0.50; 95% CI= -0.92 to -0.08; p= 0.020).Conclusion: Acupuncture therapy can lose weight in obesity cases with a Standardized Mean Different (SMD) of 0.50 compared to fake acupuncture.Keywords: acupuncture, obesityCorrespondence: Nurmila Mutiah. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: nurmilamutiah77@gmail.com.Mobile: +6287730797747.Indonesian Journal of Medicine (2021), 06(03): 325-335https://doi.org/10.26911/theijmed.2021.06.03.10